Innovative Models of Cooperation between Business Administration Majors in Universities and Enterprises - chen, yuang (Pacific International Journal, 2024)
University business administration programs strive to provide students with the skills and knowledge needed to succeed in industry. However, traditional cooperation models between universities and enterprises often fail to offer cutting-edge practical engagement. Through semi-structured interviews with Shandong Province 32 university department heads and business managers along with surveys from 217 students and employees, this mixed methods study aimed to uncover potentially innovative models of collaboration that effectively equip graduates for the modern workplace. The key findings reveal 4 collaborative archetypes deemed innovative by over three-fourths of experts, including intensive capstones with partner companies, corporate co-creation of competency frameworks integrated into curricula, rotational cross-appointments of university and company talent, and consortium advisory boards that reciprocally inform program development. Enabling success factors include aligned values, communication structures that mitigate bureaucracy, networks for talent pipeline development, and flexibility in partnership formalization. Challenges center on initial partnership development, ensuring continuity, and measuring outcomes over time horizons longer than typical academic or business quarters. By identifying best practices within these innovative collaboration models, the study provides insight into improving partnerships’ equipping of next generation corporate and entrepreneurial business leaders.